A collaborative comparison of international pediatric diabetes registries. Issue 6 (30th May 2022) - Lanzinger, Stefanie; Zimmermann, Anthony; Ranjan, Ajenthen G.; Gani, Osman; Pons Perez, Saira; Akesson, Karin; Majidi, Shideh; Witsch, Michael; Hofer, Sabine; Johnson, Stephanie; Pilgaard, Kasper A.; Kummernes, Siv Janne; et al.
Abstract: Background: An estimated 1.1 million children and adolescents aged under 20 years have type 1 diabetes worldwide. Principal investigators from seven well‐established longitudinal pediatric diabetes registries and the SWEET initiative have come together to provide an international collaborative perspective and comparison of the registries. Work Flow: Information and data including registry characteristics, pediatric participant clinical characteristics, data availability and data completeness from the Australasian Diabetes Data Network (ADDN), Danish Registry of Childhood and Adolescent Diabetes (DanDiabKids), Diabetes prospective follow‐up registry (DPV), Norwegian Childhood Diabetes Registry (NCDR), National Paediatric Diabetes Audit (NPDA), Swedish Childhood Diabetes Registry (Swediabkids), T1D Exchange Quality Improvement Collaborative (T1DX‐QI), and the SWEET initiative was extracted up until 31 December 2020. Registry Objectives and Outcomes: The seven diabetes registries and the SWEET initiative collectively show data of more than 900 centers and around 100, 000 pediatric patients, the majority with type 1 diabetes. All share the common objectives of monitoring treatment and longitudinal outcomes, promoting quality improvement and equality in diabetes care and enabling clinical research. All generate regular benchmark reports. Main differences were observed in the definition of the pediatric population, the inclusion of adults, documentation of CGM metrics and collection of raw data files as well as linkage to other data sources. The open benchmarking and access to regularly updated data may prove to be the most important contribution from registries. This study describes aspects of the registries to enable future collaborations and to encourage the development of new registries where they do not exist.